Development of Patient-Safety-Based Interprofessional Collaboration Instructional Model for the Specialist-1 of Child Health Medical Education Program - Notosoegondo, Hendriani Selina; Samsudi, Samsudi; Haryono, Haryono; Bahtera, Tjipta (The Journal of Educational Development, 2019)
This study aims to produce a patient-safety-based Interprofessional Collaboration (IPC) education model to improve the competence of the Specialist-1 of Child Health Medical Education Program (PPDS I) doctors of Child Health Medical Science in Dr. Kariadi Central Hospital, Medical School, Diponegoro University and the students in the nursing profession program. This study was designed using the Research and Development approach. The data of this study were analyzed using qualitative descriptive techniques. The steps of developing the model in this study include (1) preliminary analysis; (2) findings of factual models; (3) development of conceptual models; (4) development of a hypothetical model; (5) final model development. The results of the study show that PPDS I of Child Health at Dr. Kariadi Central Hospital has not implemented the IPC based on safety. The model of safety-based IPC is based on four main indicators, namely (1) Interprofessional Collaborative Competence; (2) Competency of Pediatricians & Nurses; (3) Interprofessional Learning Readiness Scale; (4) Scale of Interprofessional Team Performance. The results of the trials of the interprofessional collaboration education model developed have been able to increase the competence of PPDS I doctors 45.61% and 20.68% in students of the nursing profession program (nurses). The increaseof the competence and professionalism of PPDS I doctors and nurses is also based on moral principles and ethical codes that are actualized as noble attitudes and sincerity. It is suggested that the implementation of the developed patient-safety-based interprofessional collaboration education model needs to be supported by policies or regulations by related parties in order to improve the effectiveness of the specialist medical education programs and nursing professional education programs (Ners).